Risk allocation in the oil and gas contracts - Wan Zahari, Wan Mohd Zulhafiz (2016)
This research focuses on contractual mechanisms that will help to achieve a fair allocation of risk between operators and contractors. Companies that are active in the petroleum industry are exposed to substantial risks and liabilities, since they are dealing with a wide range of activities which engage volatile hydrocarbons. In this regard, most of the petroleum contracts for upstream projects depart from the common law tradition of risk allocation by shifting the risk to another party; this is done to protect commercial interests. To this end, contractual provisions are used in allocating the risks; especially those related to people, property and the environment. Risk allocation provisions deal with hypothetical events – this means that the identity of the person bearing the liability which will accrue if certain events take place is determined in advance. Such clauses are intended to ensure that, where harm arises, oil companies take responsibility for such harm and can meet the costs of mitigating that harm, including requirements for insurance and the allocation of liability. These clauses are also known as risk allocation provisions. Contractual risk allocation is one element of risk management between or among the parties involved in an undertaking. This is particularly challenging in the oil and gas industry where several parties are involved in one project. A range of risk allocations are used in oil and gas contracts, including exclusion of liability and liability caps. The research argues that the fair allocation of risk can be achieved by setting out a knock-for-knock indemnity clause in the oil and gas contracts. The methodology employed in this research will be a comparative analysis which will be carried out in a descriptive, analytic and prescriptive manner.